Public Policies of Infamy: Four Cases in Health - Mexico - Patiño, Donovan Casas; Torres, Alejandra Rodríguez; Morales, Mario Rodolfo Salazar (Archives of Community Medicine and Public Health, 2017)
This article invites to a transdisciplinary reflection, in which the policies should be part of the social benefit in this health case, here are presented four elements of analysis, maternal mortality, homicide, chronic noncommunicable diseases and ecocide. Thus these elements show a state in flight that on the one hand, ignores the real social problems in health and on the other, signs perverse pacts and creates public policies out of context dictated by neoliberal interests. In this way a transdisciplinary reflection on health is presented, where Mexico is present sailing in an infinite sea of oblivion and political perversion.